Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41467-021-27237-0
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the symmetry to suppress the Plateau–Rayleigh instability and optimize hydropower utilization

Abstract: Droplet impact on solid surfaces is essential for natural and industrial processes. Particularly, controlling the instability after droplet impact, and avoiding the satellite drops generation, have aroused great interest for its significance in inkjet printing, pesticide spraying, and hydroelectric power collection. Herein, we found that breaking the symmetry of the droplet impact dynamics using patterned-wettability surfaces can suppress the Plateau–Rayleigh instability during the droplet rebounding and impro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…Surface Wettability Gradient: Making millimeter-sized droplet move toward the designed direction is desired in wide liquid-manipulation-related [125][126][127][128][129][130][131][132][133] applications like liquid collection, [134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] printing, [151] hydropower utilization optimization [152,153] or microfluidics. [154,155] By designing a nonwetting solid surface with a wettability gradient, vertical momentum of impacting droplet can be transferred to horizontal momentum with the designed direction.…”
Section: Oblique Bouncingmentioning
confidence: 99%
“…Surface Wettability Gradient: Making millimeter-sized droplet move toward the designed direction is desired in wide liquid-manipulation-related [125][126][127][128][129][130][131][132][133] applications like liquid collection, [134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] printing, [151] hydropower utilization optimization [152,153] or microfluidics. [154,155] By designing a nonwetting solid surface with a wettability gradient, vertical momentum of impacting droplet can be transferred to horizontal momentum with the designed direction.…”
Section: Oblique Bouncingmentioning
confidence: 99%
“…Inspired by lotus leaves and beetles, wettability, especially heterogeneous wettability, provides an effective way to manipulate droplet behaviors. [19][20][21][22][23][24][25] In this work, we fabricate droplet-based springs using two parallel plates with heterogeneous wettability, and investigate their non-Hookean elastic mechanics under pressing and stretching. We demonstrate that the nonlinear behaviors of the spring can be well manipulated by the droplet volume, droplet number, and especially the wettability patterns on the parallel plates.…”
Section: Doi: 101002/smll202200875mentioning
confidence: 99%
“…Chu et al [8] reported that when the droplet impacted on the boundary between the superhydrophobic part and hydrophilic part, the directional transport distance of the droplet can be controlled by changing the proportion of the impinging droplet in the hydrophilic part. Zhao et al [9] investigated the droplet impacting on a heterogenous superhydrophobic surface with hydrophilic strips, and quantitatively manipulated the directional transport distance of the droplet and suppressed the Plateau-Rayleigh instability successfully [10]. However, these surfaces exist many defects such as droplet loss, mixing, and contamination due to the hydrophilic regions.…”
Section: Introductionmentioning
confidence: 99%